2010
DOI: 10.1128/jb.01429-09
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Alterations Explain Phenotypic Changes in Sinorhizobium meliloti Lacking the RNA Chaperone Hfq

Abstract: The ubiquitous bacterial RNA-binding protein Hfq is involved in stress resistance and pathogenicity. In Sinorhizobium meliloti, Hfq is essential for the establishment of symbiosis with Medicago sativa and for nitrogen fixation. A proteomic analysis identifies 55 proteins with significantly affected expression in the hfq mutant; most of them are involved in cell metabolism or stress resistance. Important determinants of oxidative stress resistance, such as CysK, Gsh, Bfr, SodC, KatB, KatC, and a putative peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
60
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 79 publications
7
60
2
Order By: Relevance
“…Brucella abortus hfq mutants exhibit poor expression of the sodC gene, which encodes a periplasmic Cu-Zn superoxide dismutase (39). Hfq mutants of Burkholderia cepacia (40), Moraxella catarrhalis (41), Neisseria meningitidis (42), Sinorhizobium meliloti (43), and uropathogenic E. coli (16) display enhanced sensitivity to methyl viologen, a redox-cycling agent which generates superoxide within bacterial cells. In contrast, hfq mutants of S. aureus (44) and Vibrio parahaemolyticus (45) exhibit higher resistance to oxidative stress induced by hydrogen peroxide and superoxide than does the parent strain.…”
Section: Discussionmentioning
confidence: 99%
“…Brucella abortus hfq mutants exhibit poor expression of the sodC gene, which encodes a periplasmic Cu-Zn superoxide dismutase (39). Hfq mutants of Burkholderia cepacia (40), Moraxella catarrhalis (41), Neisseria meningitidis (42), Sinorhizobium meliloti (43), and uropathogenic E. coli (16) display enhanced sensitivity to methyl viologen, a redox-cycling agent which generates superoxide within bacterial cells. In contrast, hfq mutants of S. aureus (44) and Vibrio parahaemolyticus (45) exhibit higher resistance to oxidative stress induced by hydrogen peroxide and superoxide than does the parent strain.…”
Section: Discussionmentioning
confidence: 99%
“…In the photosynthetic alphaproteobacterium Rhodobacter sphaeroides, the Hfq protein plays an important role in protection against photooxidative stress (5,6). During the past 2 years, sev-eral studies on Hfq in the plant symbiont Sinorhizobium meliloti demonstrated the importance of the RNA chaperone in cell physiology and symbiosis (3,4,24,54,60,65).…”
mentioning
confidence: 99%
“…RpoE2 is activated under a number of stress and starvation conditions and controls the transcription of Ͼ100 genes, including several involved in stress resistance (5)(6)(7)(8)(9)(10). Accordingly, rpoE2 mutants have been found to be more sensitive than the wild-type strain to desiccation and osmotic stress, as well as heat and oxidative stress in the stationary phase (6)(7)(8)11). RpoE2 orthologues, collectively called EcfG or ECF15 sigma factors (12), are widely distributed among Alphaproteobacteria, and several of them have been described as activated under stress or starvation conditions and to play various roles in stress resistance and/or host colonization (13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…However, in the alphaproteobacterial group, the prominent role of extracytoplasmic-function sigma factors was uncovered recently with the finding that RpoE2 controls a general stress response in Sinorhizobium meliloti, the nitrogen-fixing symbiont of alfalfa (5). RpoE2 is activated under a number of stress and starvation conditions and controls the transcription of Ͼ100 genes, including several involved in stress resistance (5)(6)(7)(8)(9)(10). Accordingly, rpoE2 mutants have been found to be more sensitive than the wild-type strain to desiccation and osmotic stress, as well as heat and oxidative stress in the stationary phase (6)(7)(8)11).…”
mentioning
confidence: 99%